2005
DOI: 10.1159/000083158
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Concentrations in Saliva and Dental Plaque in Relation to Caries Experience and Oral Hygiene

Abstract: The aim of the study was to determine the correlation of the antibacterial substance nitric oxide (NO) with dental caries in vivo. Salivary and dental plaque NO concentrations were analyzed by the Griess method in 11 subjects with high DMFT index and simplified oral hygiene index (OHI-S), 11 with low DMFT and OHI-S. Subjects with high DMFT and OHI-S had significantly higher NO concentrations in saliva (71.5 µM) and plaque (83.5 µM) than those with low DMFT and OHI-S (33.2 and 61.1 µM in saliva and plaque, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 32 publications
3
35
1
Order By: Relevance
“…14,15 In this sense, an increase in the TAC of saliva could produce modifications in the adherence of Streptococcus to the den tal plaque and lead to greater cariogenic activity. Several authors 16 have reported greater activity in prooxidant molecules such as nitric oxide (NO) in the saliva of subjects with dental caries. Raised levels of NO in subjects with caries and poor oral hygiene would be a defence mecha nism against increased bacterial activity in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In this sense, an increase in the TAC of saliva could produce modifications in the adherence of Streptococcus to the den tal plaque and lead to greater cariogenic activity. Several authors 16 have reported greater activity in prooxidant molecules such as nitric oxide (NO) in the saliva of subjects with dental caries. Raised levels of NO in subjects with caries and poor oral hygiene would be a defence mecha nism against increased bacterial activity in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible NOS (iNOS) is produced by macrophages that are stimulated by inflammatory cytokines, such as TNF-α, IL-1, and IFN-γ; these cytokines are able to produce NO (38). Salivary NO can be produced from free nerve endings, secretory cells in the salivary gland, salivary gland endothelial cells, and bacteria in the oral cavity (39). Salivary glands and oral microbiota play an essential role in the conversion of NO 3 − and NO 2 − to NO.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Therefore, the microbes that survive in the deeper parts of the biofilm are facultative anaerobes. This would be the reason why nitrogen oxides are significantly higher in poor oral hygiene individuals than those with good oral hygiene who have thinner dental biofilm [22]. Many anaerobic facultative bacteria synthesize nitrate reductase in low oxygen tension [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], hence, reduction can take place in the thick biofilm or deep tongue crypts [23].…”
Section: Denitrification Effect On Dental Caries Formationmentioning
confidence: 99%
“…It was reported that pH below 7 would promote the conversion of L-arginine to NO and its compounds [25]. NO is one of the byproducts and it is recognized for its antibacterial effect that inhibit the acidogenic bacteria which are responsible for caries formation [22,26]. Nitric oxide antibacterial effects are thought to include DNA modifications and interactions with other reactive species; for example, reaction with superoxide produces the highly reactive molecule peroxynitrite [27].…”
Section: Denitrification Effect On Dental Caries Formationmentioning
confidence: 99%
See 1 more Smart Citation